First biological report on Steneotarsonemus concavuscutum (Tarsonemidae): A mite inhabiting the perianth of coconut fruits - De Franca-Beltrao, Girleide V.; Araujo, Isaac feitosa; Oliveira, Henarmmany cristina alves de; Ulisses, Claudia; Ledo, Ana da silva; Lofego, Antonio C. [UNESP]; Gondim Junior, Manoel G. C. (Systematic & Applied Acarology Soc London, Natural History Museum, 2025)
Steneotarsonemus concavuscutum lives under the perianth of coconut fruits and causes necrosis, deformation, resinous lesions, and fruit abortion. Its colony develops in a shelter under the floral bracts of the fruits, which provides protection against biotic (e.g., predation) and abiotic factors (e.g., high temperature and humidity variations and influences from raindrops). However, these characteristics limit biological studies because the bracts prevent the observation of mites during their development. Aceria guerreronis also grows on the perianth of coconut fruits and has been reared using zygotic embryos (in vitro). In the present study, we performed the same procedure for S. concavuscutum. Different densities of S. concavuscutum were confined to zygotic embryos and evaluated after four weeks, with treatment involving A. guerreronis used for comparison. Steneotarsonemus concavuscutum did not develop appropriately on the zygotic embryos, unlike A. guerreronis. Subsequently, the biological aspects of S. concavuscutum were investigated by isolating the mites in arenas made from the perianth fragments of various coconut fruit varieties. An additional treatment was carried out with S. furcatus, another tarsonemid species inhabiting the perianth of fruits. The Steneotarsonemus species completed their development in arenas made of perianth fragments. A difference in developmental time betwee n sexes was observed only in S. furcatus, while no difference was detected for either Steneotarsonemus species across different varieties. Steneotarsonemus concavuscutum exhibited a longer developmental time than S. furcatus, but neither species reproduced on perianth fragments.
Keywords: Acari; coconut palm; in vitro cultivation; zygotic embryos